2017
DOI: 10.1049/iet-nbt.2016.0166
|View full text |Cite
|
Sign up to set email alerts
|

Surface adsorption of poisonous Pb(II) ions from water using chitosan functionalised magnetic nanoparticles

Abstract: In this study, chitosan functionalised magnetic nano-particles (CMNP) was synthesised and utilised as an effective adsorbent for the removal of Pb(II) ions from aqueous solution. The experimental studies reveal that adsorbent material has finer adsorption capacity for the removal of heavy metal ions. Parameters affecting the adsorption of Pb(II) ions on CMNP, such as initial Pb(II) ion concentration, contact time, solution pH, adsorbent dosage and temperature were studied. The adsorption equilibrium study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…For the wastewater having the pH in the basic range, the results are shown in Figures 6, 7 and 8. The results of wastewater treatment yield reach 100% treatment efficiencies compared to that presented in other scientific literature, which showed a yield of approximately 90% [22].…”
Section: Adsorption Experimentssupporting
confidence: 51%
See 1 more Smart Citation
“…For the wastewater having the pH in the basic range, the results are shown in Figures 6, 7 and 8. The results of wastewater treatment yield reach 100% treatment efficiencies compared to that presented in other scientific literature, which showed a yield of approximately 90% [22].…”
Section: Adsorption Experimentssupporting
confidence: 51%
“…This maximum efficiency represents a more efficient wastewater treatment comparing with other research, which revealed the obtaining of a treatment efficiency of about 30%. [22].…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Many researchers use adsorption techniques to remove the HMIs from groundwater [21][22][23][24][25][26] and help to remove the hazardous heavy metals after the contaminated source is detected. The proposed sensor platform can be used as an early warning system to identify the contaminated source at the picomolar range.…”
Section: Introductionmentioning
confidence: 99%
“…A carbon nanotubes‐based sensor also used to detect the HMIs selectively but at micromolar range [7, 8] and single‐walled boron nitride nanotube and triple‐walled boron nitride nanotube‐based biosensor simulation approach capable of detecting zeptogram of mass [9, 10] but need to check the sensitivity and complexity of the fabricated device. Many authors used Au/Ag nanoparticles (NPs) for the selective detection of mercury and other biomolecules, but measurements mainly taken in the laboratory‐based analytical instruments and on‐site detection is not possible [11–27]. The mesoporous silica‐based optical selective detection and removal of Hg 2+ ions using nanocomposite material by Shahat et al [28] is a highly pH‐dependent approach, and lower concentration in the nanomolar range is not possible.…”
Section: Introductionmentioning
confidence: 99%